Coagulation behavior of polyaluminum-titanium chloride composite coagulant with humic acid: A mechanism analysis. (15th July 2022) - Liu, Beibei; Gao, Yue; Pan, Jingwen; Feng, Qiyun; Yue, Qinyan; Guo, Kangying; Gao, Baoyu
Highlights: The binding behavior between HA and Al/Ti species at different pH was illustrated. Al hydrolysates complexed with OH and COOH to form COAl coordinate bonds. Protonation of HA affected binding behaviors due to the competition of H + for Al 3+ . PATC performed well due to the combined effects of various hydrolysates. Dominant mechanism shifted from charge neutralizing to sweep with pH increased. Abstract: The hydrolysate species of metal-based coagulants and the binding sites of humic acid (HA) are highly dependent on the pH conditions. Exploring the binding sites and modes between coagulant hydrolysates and HA molecules is critical to understanding the coagulation mechanism. In this paper, the binding behavior between HA molecules and the hydrolysates of a polyaluminum-titanium chloride composite coagulant (PATC) was investigated under different pH conditions by semi-quantitative FTIR and XPS. It was found that oligomeric and mesopolymeric hydrolysates were the dominant species under acid conditions, which could complex with the hydroxyl and carboxyl groups of HA by forming COAl/Ti coordinate bonds. However, large amounts of H + could compete with Al 3+ and weaken the removal efficiency of HA. With the increase of pH, the hydrolysis process of the PATC and the deprotonation of HA were simultaneously underway. Under weakly acid conditions, the complexation of the aluminum hydrolysates with carboxyl groups was improved due to the gradually diminishing competition of H + and the enhanced charge neutralization of the further polymerized hydrolysates. Consequently, the maximum UV254 removal by adding PATC was observed at pH 6. Under alkaline conditions, the sweeping effect of amorphous hydroxide dominated the HA removals, which was accompanied by the surface complexation of Al/Ti nuclear with carboxyl groups as well as the hydrogen bonds between hydroxyl and hydroxide. This study provides a new clue for the interaction mechanisms between the hydrolysates of composite coagulants and the dominant functional groups of HA at various pH conditions. Graphical abstract: Image, graphical abstract